Narasi Kekerasan Seksual pada Gay Anak: Negara Absen dalam Perlindungan? - Nikodimus Niko (PSGA LP2M IAIN Pontianak, 2016)
Gay were victims of sexual abuse who tends to blame and thought to be the cause of sexual violence. Sexual orientation tend to be justification the cause of action of sexual abuse. This paper describes exploration paradox of sexual violence on gay children, and act done by state in effort to protection the victims. The reseacrh method used was descriptive analysis approach. Data collection used was secondary data from literature and scientific journals. On gay children as the victim justifiying as a criminal of sexual violence because his sexual orientation.